2019
DOI: 10.1097/ta.0000000000002458
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation and comparison of the predictive ability of different frailty scores to predict outcomes in geriatric trauma patients

Abstract: BACKGROUND Different frailty scores have been proposed to measure frailty. No study has compared their predictive ability to predict outcomes in trauma patients. The aim of our study was to compare the predictive ability of different frailty scores to predict complications, mortality, discharge disposition, and 30-day readmission in trauma patients. METHODS We performed a 2-year (2016–2017) prospective cohort analysis of all geriatric (age, >65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…More than 50 tools have been developed to measure frailty [ 7 ]. Several studies have shown that frailty is associated with poorer outcomes: in the emergency department, frail patients are at increased risk of death or complications for several pathologies, such as acute coronary syndrome, trauma, pneumonia, and acute cardiac failure [ 8 12 ]. Concerning surgery, frailty was also associated with mortality, complications, and length of stay, independent of the type of surgery [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 tools have been developed to measure frailty [ 7 ]. Several studies have shown that frailty is associated with poorer outcomes: in the emergency department, frail patients are at increased risk of death or complications for several pathologies, such as acute coronary syndrome, trauma, pneumonia, and acute cardiac failure [ 8 12 ]. Concerning surgery, frailty was also associated with mortality, complications, and length of stay, independent of the type of surgery [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It takes less than 2 minutes to complete and has been validated in community-dwelling older adults to identify frail persons at risk of developing disability. 13,14 In this study, we examined the association between self-report of frailty, using an abbreviated FRAIL scale and non-home discharge (NHD), and we hypothesized that self-report of frailty as well as a positive response to individual FRAIL survey items would be associated with NHD.…”
mentioning
confidence: 99%
“…However, even in patients of the same age, there is a difference in the health status, such as the degree of independent activities or underlying diseases; therefore, there will be a difference in frailty. Recent studies reported that that the degree of frailty, which is measured by an easily accessible tool for frailty is related to trauma mortality [ 18 , 19 ]. Therefore, we expect that more meaningful results would be obtained if studies are conducted to establish the definition of elderly reflecting the degree of frailty along with age.…”
Section: Discussionmentioning
confidence: 99%